2021
DOI: 10.1088/1402-4896/ac3c5d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of thermal studies on melt quenched Ge18Bi4Se78 chalcogenide

Abstract: The crystallization characteristics for Ge18Bi4Se78 glass are studied in this work by means of differential thermal analysis (DTA) under non-isothermal conditions. One stage endothermic glass transition and one exothermic crystallization are observed in the DTA curves. The results of topological constraints for Ge18Bi4Se78 glass show that the calculated value of glass transition temperature (Tg) is very close to that of the experimental results. The as-prepared, as well as the annealed samples, are examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…%) of Sn, Se & Te respectively and CN is the coordination number of each element respectively, CN(Sn) = 4, CN(Se) = 2, CN(Te) = 2 they are calculated by 8-N rule [16]. From equation (1). Figure 1 clearly shows that <r> increases with increasing Sn content, hence, < r > lies in the range from 2.02 to 2.20.…”
Section: Average сOordination Constraints and Floppy Numbersmentioning
confidence: 98%
See 1 more Smart Citation
“…%) of Sn, Se & Te respectively and CN is the coordination number of each element respectively, CN(Sn) = 4, CN(Se) = 2, CN(Te) = 2 they are calculated by 8-N rule [16]. From equation (1). Figure 1 clearly shows that <r> increases with increasing Sn content, hence, < r > lies in the range from 2.02 to 2.20.…”
Section: Average сOordination Constraints and Floppy Numbersmentioning
confidence: 98%
“…Chalcogenides have many applications due to their specific properties such as solid-state devices, Solar cells that use amorphous thin layers., optical fiber, memory with phase change, photonics, and chalcogenide glasses (CG) [1]. Selenium-rich alloys are the most distinguished today due to their strong nonlinear optical properties, high refractive index, ideal chemical and physical properties, and high transparency in the infrared regions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in previous work [23], an x-ray energy dispersion analysis [EDAX] was performed for the asprepared Ge 18 Bi 4 Se 78 glass to ensure that the required stoichiometry of our system was achieved. It is found that the atomic percentages of Ge, Bi, and Se were 21.26, 3.79, and 74.95 at% for Ge, Bi, and Se, respectively.…”
Section: Structural Analysismentioning
confidence: 99%